2015
DOI: 10.1016/j.tust.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent changes in post-crack performance of fibre reinforced shotcrete linings

Abstract: a b s t r a c tIt is commonly assumed that when a mix achieves satisfactory performance in Quality Control tests at 28 days this result will translate into satisfactory performance throughout the design life of the corresponding concrete structure. While this is generally true of the compressive strength of concrete it is not necessarily true for other parameters. The post-crack performance of fibre reinforced concrete (FRC) differs from that of conventionally reinforced concrete in that the post-crack perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…However, there is research supporting that a significant share of the reduction on the residual tensile strength observed after exposure is related to the embrittlement of the SFRC due to densification of the matrix [13,75,99]. Since the hydration process promotes an increase on the compactness and strength of the matrix, and therefore alters the fibre-matrix bond and mechanical anchorage of the fibre, changing the failure mode from fibre pull-out to fibre yield.…”
Section: Cracksmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is research supporting that a significant share of the reduction on the residual tensile strength observed after exposure is related to the embrittlement of the SFRC due to densification of the matrix [13,75,99]. Since the hydration process promotes an increase on the compactness and strength of the matrix, and therefore alters the fibre-matrix bond and mechanical anchorage of the fibre, changing the failure mode from fibre pull-out to fibre yield.…”
Section: Cracksmentioning
confidence: 99%
“…Since the hydration process promotes an increase on the compactness and strength of the matrix, and therefore alters the fibre-matrix bond and mechanical anchorage of the fibre, changing the failure mode from fibre pull-out to fibre yield. This issue may be solved by an adequate dimensioning of the fibre type, dimensions and steel strength, considering the long-term mechanical behaviour instead of the 28 days or early age maturity one [99].…”
Section: Cracksmentioning
confidence: 99%
See 1 more Smart Citation
“…Fibres can effectively improve the mechanical properties of shotcrete and enhance the engineering properties, fatigue wear strength, postcracking toughness, and load-bearing capacity [17,18]. Shotcrete is widely used in mining and underground spatial development [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A test investigation of age-dependent changes in the mechanical properties of fibre reinforced shotcrete (FRS) round panels [28] demonstrated that macro-synthetic FRS exhibited a slight increase in the post-peak strength without any change in the fibre pull-out mechanism. On the contrary, hooked-end steel FRS exhibited a substantial decrease in the post-peak strength at increasing crack widths due to a progressive embrittlement with age, leading to fibre rupture.…”
Section: Comparison Between 3pb and 4pb Tests For 10-year Old Specimensmentioning
confidence: 99%